Effect of a care process programme on frail older people's life satisfaction. Issue 3 (11th June 2019) - Berglund, Helene; Gustafsson, Susanne; Ottenvall Hammar, Isabelle; Faronbi, Joel; Dahlin‐Ivanoff, Synneve
Abstract: Aim: The aim of this study was to analyse the effects of a full‐scale implementation of a care process programme on life satisfaction among frail older people, as compared with those receiving usual care. Design: The study includes participants from a full‐scale care process programme ( N =  77) and participants from a historical control group ( N =  66). The care process programme establishes a comprehensive continuum of care through components including case management, interprofessional teamwork and care‐planning meetings in the older people's own homes. Methods: Questionnaires were used and data were collected at baseline, with follow‐ups at three, six and 12 months. Results: The implementation of the full‐scale care process programme had a positive effect on life satisfaction among frail older people. From 6‐month–12‐month follow‐ups, a higher proportion of participants in the care process programme had positive life satisfaction outcomes, as compared with the historical control group.